Recently described and recently re-evaluated soft tissue tumours. Issue 11 (November 2015) - Khurram, Muhammad; Xie, Yan; Montgomery, Elizabeth
Abstract: Several soft tissue lesions have been recently highlighted in the medical literature. Some are recently recognized, hence often underdiagnosed because of limited knowledge whereas others have been recognized for sometime but can be viewed afresh in light of emerging molecular data. The aim of this review is to be more familiar with these entities and pathologists should consider these differential diagnosis. We discuss anastomosing haemangioma, soft tissue myoepithelial lesions, and the evolving story of myxoinflammatory fibroblastic sarcoma and other lesions that may or may not be related, namely pleomorphic hyalinizing angiectatic tumour and haemosiderotic fibrohistiocytic inflammatory lesion.